Indonesia's Geopolitical Calculation as a Middle Power in the Board of Peace Membership - Muhammad Syahdan Aprillianza; Dedy Pribadi Uang (Greenation International Journal of Law and Social Sciences, 2026)
Indonesia’s decision to join the US-led Board of Peace (BoP) on January 22, 2026, raised significant debate regarding its consistency with the nation’s bebas aktif (independent and active) foreign policy principle. However, existing literature has not systematically analyzed Indonesia’s geopolitical calculation as a middle power in this specific case. This study aims to unpack the strategic logic behind Indonesia’s BoP membership. Using a qualitative single case study design, it integrates Middle Power Theory and Foreign Policy Analysis through deductive content analysis of official documents, bilateral agreements, and think-tank reports. Three main findings emerge. First, a strong temporal correlation exists between BoP membership and the finalization of the Indonesia-US Agreement on Reciprocal Trade (ART) signed on the same day, revealing a diplomatic-economic nexus. Second, Indonesia’s choice to contribute military capabilities rather than financial fees reflects niche diplomacy logic. Third, BoP membership signals a shift from traditional non-alignment toward pragmatic multi-alignment, with the independent-active principle retained as a rhetorical frame. This study contributes to middle power literature by demonstrating that emerging middle powers prioritize strategic pragmatism over normative commitments.